Explaining, Cultural, Educational and Social Needs of Faculty Members of Farhangiyan University - According to the Predetermined Goals of Education’s Fundamental Transformation Document - Basiri, Batool; Ahmadreza Nasr; Seyedebrahim Mirshahjafar; Mahmood Mehrmohammadi (European Journal of Social Science Education and Research, 2018)
The present work is an applied and descriptive analysis survey method. Mixed techniques were applied. The Sample population in the qualitative section of the research consists of 19 thinkers; they were selected by purposeful sampling. The sample population was constituted by 181 faculty members of Farhangiyan Universities in six provinces. 150 of them were randomly selected. Research data was gathered by semi-structured interview and the researcher made the needed questionnaire. The most significant educational needs are:religious needs with emphasis on Islamic training and ethical, cultural and social needs which are discussed in four sub - categories:Cultural, Social, Ethical, Political. Quantitative results indicated that the need of such teachings is higher than intermediate level stated below. The most important need of faculty members in the cultural field is “being aware of the role of the university teachers about preserving, transferring, correcting and recreating culture”and their most important need as regards religious teaching is “the ability to use educational methods obtained from the Qoran and Nahjolbalaghe”( book of religious teachings).